Towards more transparency: The NGO LobbyControl and the German lobby register - Dieter Plehwe (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
In 2021, the German federal governing coalition, in a joint vote of the Christian Conservative (CDU/CSU) and the Social Democratic (SPD) parliamentary groups, passed a bill to introduce a German transparency register. In the United States and the European Union, such lobby registers were established much earlier. LobbyControl, a non-governmental organization (NGO) also enlisting many scientists, had long campaigned for the lobby register, which also helps expanding the opportunities for researchers to investigate lobbying activities. Dieter Plehwe describes how, 16 years after LobbyControl was founded in 2005, its work finally bore fruit.
Keywords: 300